Drosophila INDY and Mammalian INDY: Major Differences in Transport Mechanism and Structural Features despite Mostly Similar Biological Functions - Valeria Jaramillo-Martinez; Sathish Sivaprakasam; Vadivel Ganapathy; Ina L. Urbatsch (Metabolites, 2021)
INDY (I’m Not Dead Yet) is a plasma membrane transporter for citrate, first identified in Drosophila. Partial deficiency of INDY extends lifespan in this organism in a manner similar to that of caloric restriction. The mammalian counterpart (NaCT/SLC13A5) also transports citrate. In mice, it is the total, not partial, absence of the transporter that leads to a metabolic phenotype similar to that caloric restriction; however, there is evidence for subtle neurological dysfunction. Loss-of-function mutations in SLC13A5 (solute carrier gene family 13, member A5) occur in humans, causing a recessive disease, with severe clinical symptoms manifested by neonatal seizures and marked disruption in neurological development. Though both Drosophila INDY and mammalian INDY transport citrate, the translocation mechanism differs, the former being a dicarboxylate exchanger for the influx of citrate2− in exchange for other dicarboxylates, and the latter being a Na+-coupled uniporter for citrate2−. Their structures also differ as evident from only ~35% identity in amino acid sequence and from theoretically modeled 3D structures. The varied biological consequences of INDY deficiency across species, with the beneficial effects predominating in lower organisms and detrimental effects overwhelming in higher organisms, are probably reflective of species-specific differences in tissue expression and also in relative contribution of extracellular citrate to metabolic pathways in different tissues